Perancangan Desain Label Kemasan, Company Profile, dan Standing Banner untuk Meningkatkan Nilai Jual Produk “Maznah Nais” - Latifatuz Zahro; Nurul Hikmah; M. Riyadus Solihin; Ahmad Faruq Faza Binnaja; Nadya Putri Maulina; Hendian Oritza Anugrah Nastiti (Jurnal PkM (Pengabdian kepada Masyarakat), 2023)
The Maznah Nais product is a homemade light snack product produced by the Tawang Jaya company located in Tawangrejeni Village, Turen District, Malang Regency. This brand has very good quality but only limited to the scope of people close to the owner of the company. The production tools used are still manual so that the products produced are limited. Meanwhile, to buy a more up-to-date tool requires a lot of money. Even though Maznah Nais has good selling quality. Therefore, in order to increase the selling quality of this product, it is necessary to have the latest packaging labels, design a company profile for promotional media to establish cooperation with various investors, and make standing banners or X banner to make it easier to sell offline. Based on the problems encountered, this service takes an approach using qualitative methods. Through interviews, observation, and literature studies. The results obtained were renewal of packaging labels, company profiles, and standing banner